Minat Mahasiswa Menjadi dan Tidak Menjadi Akuntan Publik - Semara Putra, Gede Adi; Ardiana, Putu Agus (E-Jurnal Akuntansi; Vol 33 No 6 (2023), 2023)
The aim of this research is to find out the factors that differentiate the interests of students of the Bachelor of Accounting Study Program at Udayana University between those who wish and those who do not wish to engage in the public accounting profession based on Maslow's theory of motivation. The study used the census method with a sample of 262 students of the Udayana University Bachelor of Accounting Study Program who participated in the survey. Research data was collected using a questionnaire instrument based on Google Forms which was distributed via social media Line Group class 2015 to 2021. The data collected was then analyzed using discriminant analysis. The results showed that physiological needs and appreciation needs significantly differentiated students' interest in becoming and not becoming public accountants, while safety needs, social needs and self-actualization needs did not significantly differentiate students' interests in becoming and not becoming public accountants. Keywords: Student Interests; Public Accountants; Maslow's Motivation Theory; Discriminant Analysis